Atlantic Forest Regeneration Dynamics Following Human Disturbance Cessation in Brazil - Sivisaca, Deicy Carolina Lozano [UNESP]; Puglla, Celso Anibal Yaguana [UNESP]; Passos, José Raimundo de Souza [UNESP]; Fonseca, Renata Cristina Batista [UNESP]; Ganga, Antonio; Capra, Gian Franco; Guerrini, Iraê Amaral [UNESP] (MDPI, 2024)
The Brazilian Atlantic Forest (BAF) is one of the most important biodiversity hotspots and species-rich ecosystems globally. Due to human activities, it has been significantly reduced and fragmented. This study examined both biotic (floristic composition, diversity, and structure) and abiotic (topographic and soil) factors in BAF fragments undergoing varying levels and durations of human disturbance cessation: approximately 20 years (20 y), ~30 years (30 y), and over 40 years (>40 y). We aimed to understand the recovery dynamics of floristic composition, diversity, and structure in BAF fragments in relation to abiotic factors. Several statistical tools were employed to examine similarities/differences and relationships. Forests of the 30 y group exhibit significantly greater homogeneity in terms of floristic composition, while forests of the 20 y group are characterized by lower species abundance and diversity. The floristic composition was primarily influenced by soil features and the time of disturbance. Under “Environmental Protection Areas”, soil–vegetation recovery can occur more swiftly than usually observed for BAF. A significant BAF recovery was observed approximately 40 years after the end of human disturbance. A partial recovery featured 30 y disturbed areas, while in 20 y forests, recovery is in its early stages. Human-disturbed BAF can gradually rebound when effective management practices are implemented.
Keywords: conservation and management; environmental protection areas; indicator species; multivariate statistics; soil; vegetation